2007
DOI: 10.1089/ars.2007.9.271
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Transport Regulation in Leukemic Cells: How Can H2O2 Mimic Stem Cell Factor Effects?

Abstract: In leukemic cells, glucose transport is activated by SCF and H2O2 through a common signal cascade involving Akt, PLCgamma, Syk, and the Src family, in this order. An explanation can be provided by the phosphorylation of c-kit, the SCF receptor, elicited by either SCF or H2O2. Moreover, antioxidants prevent the SCF effect on glucose transport, confirming the involvement of H2O2 in the pathway leading to glucose-transport activation and suggesting a potential role for reactive oxygen species in leukemia prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
1
12
1
Order By: Relevance
“…Moreover, the high proliferative capacity of murine embryonic stem cells was shown to be closely correlated with the high activity of different glycolytic enzymes, elevated glycolytic flux, and low mitochondrial oxygen consumption (25). In leukemic cells, glucose transport is activated by stem cell factor and H 2 O 2 , suggesting a potential role for ROS in leukemia proliferation (29). NADPH oxidase plays an important role in promoting the proliferation of skeletal muscle precursor cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the high proliferative capacity of murine embryonic stem cells was shown to be closely correlated with the high activity of different glycolytic enzymes, elevated glycolytic flux, and low mitochondrial oxygen consumption (25). In leukemic cells, glucose transport is activated by stem cell factor and H 2 O 2 , suggesting a potential role for ROS in leukemia proliferation (29). NADPH oxidase plays an important role in promoting the proliferation of skeletal muscle precursor cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…Cell viability was also assayed by the MTT assay [23], since the reduction of tetrazolium salts is widely accepted as a reliable way to examine cell viability/proliferation. Cells were incubated with 0.5 mg/mL MTT for 4 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…It has recently been reported that in a human neuronal cell line, SH-SY5Y, GLUT1 translocation in response to insulin-like growth factor (IGF-I) occurs [27] and, for the first time in a neuronal cell system, also GLUT4 is translocated to the plasma membrane in response to insulin [28]. We have been studying for a long time the glucose transport activity in many leukaemia cell lines expressing mainly GLUT1, demonstrating that, also in these cell types, GLUT1 is recruited on the plasma membrane from intracellular compartments in response to different stimuli, greatly enhancing the rate of glucose uptake [29, 30]. Moreover, it is well known that impaired GLUT4 translocation is causally linked to insulin resistance and consequently to noninsulin-dependent diabetes mellitus [31, 32].…”
Section: Introductionmentioning
confidence: 99%